Microstructure and wear properties of electron beam melted Ti-6Al-4V parts : a comparison study against as-cast form - Wang, Pan (2018)
Ti-6Al-4V (Ti64) parts of varying thicknesses were additively manufactured (AM) by the powder-bed-based electron beam melting (EBM) technique. Microstructure and wear properties of these EBM-built Ti-6Al-4V parts have been investigated in comparison with conventionally cast Ti64 samples. Sliding wear tests were conducted using a ball-on-disc micro-tribometer under ambient conditions. Experimental results reveal that EBM-built Ti64 samples exhibited higher microhardness and an overall larger coefficient of friction as compared to the as-cast counterpart. Of interest is that the corresponding specific wear volumes were lower for EBM-built Ti64 samples, while the as-cast Ti64 showed the poorest wear resistance despite its lower coefficient of friction. Wear mechanisms were provided in terms of quantitative microstructural characterization and detailed analysis on coefficient of friction (COF) curves.